(untitled) (Journal of Forensic Medicine & Toxicology, 2012)
The present study was carried out on the measurements of fingers length and body height of total 103students between 21 to 32 years of age. The study was carried out in the Department of Forensic Medicine and toxicology at Pt. B.D. Sharma PGIMS, Rohtak, Haryana State, India. A total number of 103 (52 males, 51 females) medical students of state of Haryana were included in the study. Anthropometric measurements were taken by using standard anthropometric instruments in centimeters to the nearest millimeter. All the measurements were taken in a well lighted room. Obtained data was analysed and attempt was made to find out correlation and to derive a regression formula between finger length and height of an individual. A good correlation of height was observed with fingers length and it was statistically highly significant. The results of the present study would be useful for Anthropologists and Forensic Medicine Experts.